Kepuasan Nasabah BPR Ditinjau Dari Kualitas Pelayanan Dan Citra Bank - Desta Ayu Mustika Sari; Imam Baehaqi (Universitas Islam Kadiri, 2021)
Customer satisfaction is the extent to which a product’s perceived pervormance matches a buyer’s expectations. If the product’s performance falls short of expectations the customers is dissatisfied. If performance matches expectations, the customers is satisfied. This study aims to determine the effect of service quality and corporate image on customer satisfaction. This study uses quantitative methods. The population in this study amounted to 3,209 customers of PT BPR SumberdhanaAnda Rejotangan branch. The number of samples was calculated using the slovin formula with the results of 97 respondents. The sampling technique used in this study is proportional random sampling, and the type of sampling used is simple random sampling. This study using analysis descriptive statistical analysis, classical assumption tests and multiple linear regression analysis techniques. The study results found a partial effect of service quality on customer coverage and company image on customer satisfaction. Moreover, there is a simultaneous influence of service quality and corporate image on customer satisfaction.